Antithrombin III Contributes to the Protective Effects of Fresh Frozen Plasma Following Hemorrhagic Shock by Preventing Syndecan-1 Shedding and Endothelial Barrier Disruption. Issue 2 (February 2020) - Lopez, Ernesto; Peng, Zhanglong; Kozar, Rosemary A.; Cao, Yanna; Ko, Tien C.; Wade, Charles E.; Cardenas, Jessica C.
ABSTRACT: Background: Endothelial dysfunction during hemorrhagic shock (HS) is associated with loss of cell-associated syndecan-1 (Sdc1) and hyperpermeability. Fresh frozen plasma (FFP) preserves Sdc1 and reduces permeability following HS, although the key mediators remain unknown. Antithrombin III (ATIII) is a plasma protein with potent anti-inflammatory and endothelial protective activity. We hypothesized that the protective effects of FFP on endothelial Sdc1 and permeability are mediated, in part, through ATIII. Methods: ATIII and Sdc1 were measured in severely injured patients upon admission (N = 125) and hospital day 3 (N = 90) for correlation analysis. In vitro effects of ATIII on human lung microvascular endothelial cells (HLMVECs) were determined by pretreating cells with vehicle, FFP, ATIII-deficient FFP, or purified ATIII followed by TNFα stimulation. Sdc1 expression was measured by immunostaining and permeability by electrical impedance. To determine the role of ATIII in vivo, male mice were subjected to a fixed pressure exsanguination model of HS, followed by resuscitation with FFP, ATIII-deficient FFP, or ATIII-deficient FFP with ATIII repletion. Lung Sdc1 expression was assessed by immunostaining. Results: Pearson correlation analysis showed a significant negative correlation between plasma levels of Sdc1 and ATIII (R = −0.62; P < 0.0001) in injured patients on hospital day 3. Also, i n vitro, FFP and ATIII prevented TNFα-induced permeability ( P < 0.05 vs TNFα) in HLMVECs. ATIII-deficient FFP had no effect; however, ATIII restoration reestablished its protective effects in a dose-dependent manner. Similarly, FFP and ATIII prevented TNFα-induced Sdc1 shedding in HLMVECs; however, ATIII-deficient FFP did not. In mice, Sdc1 expression was increased following FFP resuscitation (1.7 ± 0.5, P < 0.01) vs. HS alone (1.0 ± 0.3); however, no improvement was seen following ATIII-deficient FFP treatment (1.3 ± 0.4, P = 0.3). ATIII restoration improved Sdc1 expression (1.5 ± 0.9, P < 0.05) similar to that of FFP resuscitation. Conclusions: ATIII plays a role in FFP-mediated protection of endothelial Sdc1 expression and barrier function, making it a potential therapeutic target to mitigate HS-induced endothelial dysfunction. Further studies are needed to elucidate the mechanisms by which ATIII protects the endothelium.